1997
DOI: 10.1152/ajpheart.1997.273.5.h2224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high glucose on vascular endothelial growth factor expression in vascular smooth muscle cells

Abstract: Vascular endothelial growth factor (VEGF), in addition to its growth-promoting effects on endothelial cells, can also increase vascular permeability and monocyte migration. It has therefore been implicated in the pathogenic neovascularization associated with diabetic retinopathy and atherosclerosis. However, the factors regulating VEGF expression in the vascular wall are not fully understood. In this study, we examined the regulation of VEGF expression in vascular smooth muscle cells (VSMC) by hyperglycemia as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
99
3
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 42 publications
(56 reference statements)
2
99
3
2
Order By: Relevance
“…ACE inhibitors attenuate the formation of angiotensin II and the break-down of bradykinin. Studies in vitro have shown that angiotensin II is able to stimulate the expression of VEGF in bovine retinal pericytes [20], rat heart endothelial cells [26], as well as human vascular smooth muscle [10,16,17] and mesangial cells [18,19]. Moreover, increased concentrations of angiotensin II have been found in the vitreous fluid of patients with proliferative diabetic retinopathy [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ACE inhibitors attenuate the formation of angiotensin II and the break-down of bradykinin. Studies in vitro have shown that angiotensin II is able to stimulate the expression of VEGF in bovine retinal pericytes [20], rat heart endothelial cells [26], as well as human vascular smooth muscle [10,16,17] and mesangial cells [18,19]. Moreover, increased concentrations of angiotensin II have been found in the vitreous fluid of patients with proliferative diabetic retinopathy [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of HIF-1a induction by angiotensin II depends on the production of reactive oxygen species [17]. The observation that hyperglycaemia is required to detect angiotensin II-induced expression of VEGF in cultured smooth muscle cells [16] could also be related to the formation of radicals, because of an altered cellular redox state induced by hyperglycaemia. These in vitro observations agree closely with earlier in vivo observations in rat aorta, namely that infusion of angiotensin II increases the production of superoxide anions by activation of NADPH oxidase, an effect that could be blocked completely by losartan [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most potent stimulator of VEGF that has been found is hypoxia [124,136] but in mesangial cells angiotensin II has been shown to stimulate VEGF, a process that is blocked by co-incubation of losartan, an angiotensin 1 receptor antagonist [133±135]. High glucose concentration has been shown to stimulate VEGF expression in vascular smooth muscle cells [137], probably through PKC stimulation [138]. In addition, phorbol esters stimulate mesangial VEGF production [139] and notably, inhibition of PKC blocks VEGF signalling [140].…”
Section: In Vitro Evidence For Vegf Effects On Kidney Cellsmentioning
confidence: 99%